FUNCTIONS OF VANDALISM IN YOUTH BEHAVIOUR: FROM PERSONALITY TO SOCIETY - O. V. Kruzhkova; I. V. Vorobyeva; R. Yu. Porozov; B. Zarbova (Russian State Vocational Pedagogical University, 2018)
Introduction. Graphic vandalism has become a widespread phenomenon in the space of modern cities. Traditionally, vandalism has been assessed as a negative phenomenon, leading to the destruction of the material, visual and social environment of urban public space. Recently, however, the discourse on the positive meaning of certain forms of vandalism (graffiti, street art, etc.) has been activated. At the same time, there is no discussion of the role and influence of vandalism on public and individual life, although, like any socio-cultural and socio-psychological phenomenon, vandalism has the basis and carries certain messages.The aim of this research was to identify and describe the functions of graphic vandalism, taking into account socio-cultural and socio-psychological aspects.Methodology and research methods. The study was conducted in the spatial environment of the megalopolis (Ekaterinburg, Russia) by photographing results of vandal acts (more than 6000 photographs) with subsequent trace-assessment and content analysis of images.Results and scientific novelty. The structural functions of vandalism at the socio-environmental and individual-subjective levels are identified and characterised. The signalling and designing functions, preparation of social changes and management of public mood are referred to the first level. At the second (individual-subjective) level, the demonstrative-and-protest function, functions of reactions, compensation and self-expression are allocated. The functions are illustrated with the examples of visual representations. A two-dimensional model of vandalism functions is formed, where the functions are distributed in the spaces of "construction / reconstruction", "emotional regulation / moral regulation". It is noted that any function of vandal activity at the individual level becomes a kind of marker "points of tension" at the socio-environmental level. The functional variety of vandalism becomes the reason of its ambiguous perception with diverse and occasionally contradictory estimates. The authors came to the conclusion that vandalism is socially considered as the evolutionary managerial instrument of social development, which is capable to weaken impermeability of the normatively and traditionally established limits, providing adjustability of the cultural and material environment in the conditions of innovative and mobilisation changes of society. From the perspective of the personality, vandalism is concerned as individual behaviour over the socially defined limits of activity among ordinary members of the society. Thus, vandalism as the phenomenon of public life acts as a norm and a deviation, to which an assessment is given in dependence on functional significance and subject self-identification of the specific vandal act.Practical significance. The research materials and the results obtained can be used to improve and optimise the technologies for management youth vandal activity in megapolises, for prevention and sublimation of destructive forms of youth behaviour in an urban environment.